1996
DOI: 10.1177/140349489602400107
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic symptoms in human service work

Abstract: This study reports on subjective health of personnel in human services and other occupations. A mail questionnaire was sent to 8296 employees in the Social Insurance Organization (SIO) and the Individual and Family Care (IFC) in social welfare agencies. The response rate was 69.1% or 5730 persons. Perceived health was measured by a standard form widely used in occupational health services, FHV004D, here split into four principal components, indicating psycho-vegetative, musculoskeletal, immunological, and gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Because of the requirement of anonymity no formal non-participation analysis could be done, but indirect data from the larger project [2]did not indicate a major bias due to differences in sociological characteristics between participants and non-participants, as pointed out above. However, in a correlation study a complete participation is not needed, provided that the sample is not biased by self-selection, but the strength of the associations may be weakened by drop-outs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the requirement of anonymity no formal non-participation analysis could be done, but indirect data from the larger project [2]did not indicate a major bias due to differences in sociological characteristics between participants and non-participants, as pointed out above. However, in a correlation study a complete participation is not needed, provided that the sample is not biased by self-selection, but the strength of the associations may be weakened by drop-outs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the participants had responded twice to the questionnaire on job conditions, first in the large project and then in the present study. The response rate of the large project was 69.9% and non-participation was found to be random in a non-response analysis [2]. Aggregate responses from the two study occasions could thus be compared, showing whether the participants in this study were different.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Though there is basically no profession that is free from some level of burnout, professions such as medical, teaching, banking, and managers have been known to have a higher risk of burnout than others. [8] Studies have shown an incidence of up to 30% burnout syndrome among teachers [9] and 10% for health professionals. [10] These professions are people-oriented (interactions with other people; clients, students, customers, patients etc.)…”
Section: Introductionmentioning
confidence: 99%